Contractual responses to the common pool: prorationing of crude oil production - Libecap, Gary D.; Wiggins, Steven N. (American Economic Review, 1984)
This paper examines bargaining among firms to mitigate rent dissipation following the major oil discoveries of 1926-35. Because of high bargaining costs, firms chose prorationing instead of consolidation and unitization, and success varied. The analysis also shows that prorationing took the form it did because concession, such as per well quotas, were required to draw in small operations and the quotas led to predictable responses regarding rent dissipation. Prorationing, despite its costs, controlled total field production and costs, conserved natural reservoir energies, and lengthened field life. When private agreements failed, the parties successfully appealed for state enforcement. Since similar heterogeneities influnce regulations elsewhere in the economy, detailed analysis of bargaining among firms is essential for insight into the emergence of various institutional forms. 33 references, 3 tables.